Domain wall motion and Barkhausen effect in magnetic nanoparticles for EOR applications - Baig, M.K. (American Institute of Physics Inc., 2016)
The domain wall motion in magnetic nanoparticles is a useful parameter of study. The subject of this research is to study of the phenomenon of discontinuous domain wall motion, or the Barkhausen Effect in magnetic nanoparticles. In this work hematite (Fe2O3) nanoparticles have been synthesized using sol-gel auto-combustion and characterized using X-ray diffraction, Field emission scanning electron microscopy (FESEM), Transmission electron microscope (TEM) and Vibrating sample magnetometer (VSM) for crystal structure, morphology, shape, size and magnetic properties respectively. The FESEM and TEM results show that the particles are spherical in nature and average size is 60nm that is suitable for domain walls and barkhuasen effect. The VSM results show high coercivity 175 Oe and low saturation magnetization due to domain wall pinning and barkhausen effect. The size and magnetic properties reveals the existence of domain walls in the synthesized sample. The magnetic properties confirm the energy losses due to domain wall pinning, discontinuous domain rotation or barkhausen effect during magnetization which is useful for oil-water interfacial tension reduction and viscosity of oil. The high surface charge of magnetic nanoparticles and adsorption at the rock surface is useful for wettability alteration of rocks. Â© 2016 Author(s).